Exercise induced immune regulation and drug efficacy in rhinitis nasopharyngeal carcinoma implications for tumor microenvironment single cell immune signal transduction - He, Guanwen; Bao, Weijing; Yang, Jiansheng; Guo, Xiuqin; Lu, Wenxian; Ji, Xiuhui; Gao, Shang; Wei, Rifu; Chen, Yisheng (Frontiers in Immunology, 2025)
Emerging evidence reveals that exercise modulates immune signaling to enhance the efficacy of immunotherapy in diseases like allergic rhinitis (AR) and nasopharyngeal carcinoma (NPC). By influencing immune cell trafficking, reprogramming inflammatory pathways within the tumor microenvironment (TME), and altering drug pharmacokinetics, exercise improves immune responses and therapeutic outcomes. Exercise enhances immune cell activation and infiltration into tumors, modulates checkpoint and cytokine signaling cascades, and mitigates treatment-related side effects, thereby improving patient compliance. Recent advancements in single-cell technologies, such as single-cell RNA sequencing and spatial omics, provide unprecedented insights into immune cell heterogeneity and signal transduction dynamics in the TME, uncovering new targets for exercise-modulated therapies. This review explores the synergistic effects of combining exercise with immune-based therapies, particularly in cancer treatment, highlighting the role of exercise in reshaping TME inflammation, overcoming immune evasion, and enhancing immune-mediated drug bioavailability. Personalized exercise regimens, tailored to individual patient profiles, are critical for optimizing therapeutic responses. Integrating exercise with immunotherapy, guided by single-cell and systems-level analyses, may provide a transformative approach for improving the clinical outcomes of AR and NPC patients, paving the way for more effective, individualized cancer treatments.